QOL-23. TOWARDS PATIENT-REPORTED OUTCOME ASSESSMENT IN THE MOLECULAR TUMOR BOARD – CANCER PATIENTS UNDER TARGETED THERAPY: APP-BASED ASSESSMENT OF PATIENT-REPORTED OUTCOMES (TRACE). (14th November 2022) - Renovanz, Mirjam; Bombach, Paula; Grosse, Lucia; Rieger, Johannes; Skardelly, Marco; Rieger, David; Hille, Hanni; Volkmer, Sebastian; Dörner, Lorenz; Kurz, Sylvia; Hippler, Melina; Paulsen, Frank; et al.
Abstract: Comprehensive genomic profiling and biomarker-based therapeutic strategies are currently used in clinical trials and in innovative health care systems including the center for personalized medicine network. Systematic assessments of patient-reported outcomes are warranted to gain insight into the perspective of patients and their relatives during biomarker-based therapies. In the present study, we focused on health-related quality of life (HRQoL), psychosocial situation, and physical symptoms in patients treated at the Center for Personalized Medicine Tübingen. First, we retrospectively evaluated symptom burden of n=265 (neuro-)oncological patients in the Molecular Tumor Board (MTB). Sixty percent of patients reported at least 1 neurological symptom, and psychosocial burden/unmet needs were high (overall 156/265; 59%, patients with malignant tumors n=86/106; 81%, Fisher's exact, p < 0.0001). We therefore developed an app by 14 expert rounds and pretesting including validated assessments of HRoL, symptom und psychological burden and tested it in a pilot study. We conducted a structured interview with users 3 months afterwards to assess the app's usability and feasibility. The interview was transcribed and analyzed according to a qualitative content analysis. So far, a total of 10 patients and caregivers have been enrolled in this pilot study. They reported that (i) the app is compatible with their daily routine (median 9.3, range 0-10), that (ii) they are more aware of their health status, which was rated as positive, and that (iii) completing app-based questionnaires was easier compared to paper questionnaires. Two patients reported technical problems, which were resolved timely. The pilot study proved feasibility and acceptance of the app. The app might optimize symptom burden assessment, adapted to the patients' profiles. The next step is to prospectively compare HRQoL before and after start of targeted therapy in a multicenter study.